Self-directed learning strategies in adult educational contexts - Giuseffi, Francesco G., 1972- (Advances in higher education and professional development (AHEPD), 2019)
"This book examines how self-directed learning methods and strategies is impacting adult learning in various formal and informal learning situations and educational encounters. It also explores theories and research-based learning strategies that are self-directed in nature and to find connections to enhance various connections to adult learning"--